3D printed ceramic slurries with improved solid content through optimization of alumina powder and coupling agent. (April 2021) - Li, He; Liu, Yongsheng; Liu, Yansong; Zeng, Qingfeng; Liang, Jingjing
Abstract: Stereolithography based-3D printing technology requires ceramic slurries with high solid content and low viscosity to prevent the formation of cracks, holes, warping, and other defects in sintered ceramic parts. In this study, several approaches based on optimization of alumina powder and coupling agent were explored to improve the solid content of ceramic slurries. It was shown that slurries containing γ-Al2 O3 reached solid content of only 22.5 wt% and viscosity of 15, 199 mPa·s. By comparison, slurries composed of α-Al2 O3 reached higher solid content of 75 wt% and viscosity of 12, 780 mPa·s. Three types of coupling agents, namely (3-Aminopropyl) triethoxysilane, (Aminoethylamino) propyldimethoxymethylsilane and 3-(Trimethoxysilyl) propyl methacrylate (abbreviated as E, F and G, respectively) were used to reduce the viscosity of the slurries. The addition of 10 wt% G led to slurry solid content reaching 82 wt% and viscosity of 860 m·Pas. The significant decrease in viscosity was mainly attributed to the presence of bifunctional hydrolyzable groups in G, which could well attach to alumina. On the other hand, the presence of organo-functional groups might also well attach to the photosensitive resin. The ceramics prepared with γ-Al2 O3 exhibited numerous pores in both intraparticle and intergranular while those obtained with α-Al2 O3 showed pores in only intergranular. The porous structure in γ-Al2 O3 occupied large space, leading to low solid content. Ceramics prepared with 75 wt% solid content possessed flexural strength of 29.3 MPa, bulk density of 2.3 g/cm 3 and open porosity of 39.8 %. By comparison, ceramics prepared with 82 % solid content showed flexural strength of 45.0 MPa. In sum, these findings look promising for future preparation of high-solid content 3D printed ceramic slurries for complex ceramics, such as ceramic cores.